Answer:
These two equations are equal because they both simplify to:
(38x)^(7) = (3222x)^(7) = 3^(7)*2^(7)*2^(7)*x^(7)
and
6^(7)4^(7)x^(7) = (23)^(7)(2^2)^(7)*x^(7) = 2^(7)*3^(7)*2^(14)*x^(7) = 3^(7)*2^(21)*x^(7)
So, we have:
3^(7)*2^(7)*2^(7)*x^(7) = 3^(7)*2^(21)*x^(7)
Cancelling out x^(7) from both sides, we get:
3^(7)*2^(7)*2^(7) = 3^(7)*2^(21)
Simplifying, we get:
2^(7)*2^(7) = 2^(21)
which is true since 2^(7)2^(7) = (2222222)(2222222) = 2^(14), and 2^(21) = (2222222222222)(222222222222*2) = 2^(14)*2^(7).